Does light level vision noise disturbance and fatigue effect the shooting rates of futsal players - Yücel Ocak; Raşit Sert (Instituto Brasileiro de Pesquisa e Ensino em Fisiologia do Exercício, 2021)
In this study, it has been aimed to see if there is any effects of the foreseeable inconstant on the percentage of shots in a competitive environment and if so, to see the qualities of these effects.  22 volunteer's male futsal player between the ages of 18-28 that have been playing futsal for at least four years in Afyon Kocatepe University futsal team have participated in this study. In the study which is players in isolated light environment, the shot percentage in isolated low light environment the shot percentage in environments with noise and image disturbance behind the goal and the shot percentage of after having been exhausted, are evaluted.  While evaluating the acquifed data, the relationship between the varriables are examined with the help of Pearson Correlation Analyze; an Covariance Analyze (ANCOVA) is used for comparison of variables.  When analyzed the average percentage of the shot hits which have been done in different environment. It has been seen that the highest shot hit average occurs in isolated normal light environment. It has been notice that the shot hits that have been done in isolated low light environments with noise and image disturbance behind the goal have lower averages.  As a conclusion, in a competetive environment it has been notice that it foreseeable inconstants have negative effects on the shot hit percentage averages.